Anaemia in HIV‐infected pregnant women receiving triple antiretroviral combination therapy for prevention of mother‐to‐child transmission: a secondary analysis of the Kisumu breastfeeding study (KiBS). Issue 3 (22nd January 2016) - Odhiambo, Collins; Zeh, Clement; Angira, Frank; Opollo, Valarie; Akinyi, Brenda; Masaba, Rose; Williamson, John M.; Otieno, Juliana; Mills, Lisa A.; Lecher, Shirley Lee; Thomas, Timothy K.
Abstract: Objective: The prevalence of anaemia during pregnancy is estimated to be 35–75% in sub‐Saharan Africa and is associated with an increased risk of maternal mortality. We evaluated the frequency and factors associated with anaemia in HIV‐infected women undergoing antiretroviral (ARV) therapy for prevention of mother‐to‐child transmission (PMTCT) enrolled in The Kisumu Breastfeeding Study 2003–2009. Methods: Maternal haematological parameters were monitored from 32 to 34 weeks of gestation to 2 years post‐delivery among 522 enrolled women. Clinical and laboratory assessments for causes of anaemia were performed, and appropriate management was initiated. Anaemia was graded using the National Institutes of Health Division of AIDS 1994 Adult Toxicity Tables. Data were analysed using SAS software, v 9.2. The Wilcoxon two‐sample rank test was used to compare groups. A logistic regression model was fitted to describe the trend in anaemia over time. Results: At enrolment, the prevalence of any grade anaemia (Hb < 9.4 g/dl) was 61.8%, but fell during ARV therapy, reaching a nadir (7.4%) by 6 months post‐partum. A total of 41 women (8%) developed severe anaemia (Hb < 7 g/dl) during follow‐up; 2 (4.9%) were hospitalised for blood transfusion, whereas 3 (7.3%) were transfused while hospitalised (for delivery). The greatest proportion of severe anaemia events occurred around delivery (48.8%; n = 20). Anaemia (Hb ≥ 7 and < 9.4 g/dl) at enrolment was associated with severe anaemia at delivery (OR 5.87; 95% CI: 4.48, 7.68, P < 0.01). Few cases of severe anaemia coincided with clinical malaria (24.4%; n = 10) and helminth (7.3%; n = 3) infections. Conclusion: Resolution of anaemia among most participants during study follow‐up was likely related to receipt of ARV therapy. Efforts should be geared towards addressing common causes of anaemia in HIV‐infected pregnant women, prioritising initiation of ARV therapy and management of peripartum blood loss.